Unusual formation of hollow NiCoO2 sub-microspheres by oxygen functional group dominated thermally induced mass relocation towards efficient lithium storage. Issue 30 (17th July 2019) - Wang, Zhengluo; Denis, Dienguila Kionga; Zhao, Zhiwei; Sun, Xuan; Zhang, Jinyang; Hou, Linrui; Yuan, Changzhou
Abstract : The unique oxygen functional group dominated thermally induced mass relocation strategy was first purposefully explored for controllable synthesis of uniform NiCoO2 hollow spheres with enhanced lithium-storage behaviors for LIBs. Abstract : Hollow architectures have attracted tremendous interest for electrochemical energy storage applications thanks to their fascinating physicochemical merits. The purposeful exploration of efficient methodologies for fabricating hollow multi-composition oxide structures is an everlasting topic for electrochemists and materials scientists. In this contribution, we first devised a novel oxygen functional group dominated thermally induced mass relocation synthesis of binary NiCoO2 hollow sub-microspheres (NCOHSs). The requisite role of partial removal of oxygen-enriched organic species in the NiCo-glycerate precursor was rationally put forward for smart synthesis of phase-pure NCOHSs. By virtue of their compositional and structural advantages, the resultant NCOHSs exhibited superior high-rate lithium storage performance, when utilized as a competitive anode for Li-ion batteries (LIBs). Encouragingly, a large reversible capacity of ∼805.9 mA h g −1 was retained by the NCOHSs after 750 cycles at 500 mA g −1, and even ∼492.4 mA h g −1 at a high current rate of 2 A g −1 . Furthermore, the NCOHS-based full device delivered an energy density of ∼204.6 W h kg −1, highlighting its appealing application in advanced LIBs. More significantly, we strongly envision that the unusual hollow formation mechanism proposed here will hold huge promise in enriching synthetic strategies of hollow binary metal oxide architectures for energy-related applications.